Inflammatory Blood Biomarker Kynurenine Is Linked With Elevated Neuroinflammation and Neurodegeneration in Older Adults: Evidence From Two 1H-MRS Post-Processing Analysis Methods - Vints, Wouter A. J.; Kušleikiene, Simona; Sheoran, Samrat; Šarkinaite, Milda; Valatkevičiene, Kristina; Gleizniene, Rymante; Kvedaras, Mindaugas; Pukenas, Kazimieras; Himmelreich, Uwe; Cesnaitiene, Vida J.; Levin, Oron; Verbunt, Jeanine; et al. (Frontiers in Psychiatry, 2022)
Rationale and Objectives: Pro-inflammatory processes have been argued to play a role in conditions associated with cognitive decline and neurodegeneration, like aging and obesity. Only a limited amount of studies have tried to measure both peripheral and central biomarkers of inflammation and examined their interrelationship. The primary aim of this study was to examine the hypothesis that chronic peripheral inflammation would be associated with neurometabolic changes that indicate neuroinflammation (the combined elevation of myoinositol and choline), brain gray matter volume decrease and lower cognitive functioning in older adults. Materials and methods: Seventy-four older adults underwent bio-impedance body composition analysis, cognitive testing with the Montreal Cognitive Assessment (MoCA), blood serum analysis of inflammatory markers interleukin-6 (IL-6) and kynurenine, magnetic resonance imaging (MRI) and proton magnetic resonance spectroscopy (1H-MRS) of the brain. Neurometabolic findings from both Tarquin and LCModel 1H-MRS post-processing software packages were compared. Regions of interest for MRI and 1H-MRS measurements were dorsal posterior cingulate cortex (DPCC), left hippocampal cortex (HPC), left medial temporal cortex (MTC), left primary sensorimotor cortex (SM1) and right dorsolateral prefrontal cortex (DLPFC). Results: Elevated serum kynurenine levels were associated with signs of neuroinflammation, specifically in the DPCC, left SM1 and right DLPFC, and signs of neurodegeneration, specifically in the left HPC, left MTC and left SM1, after adjusting for age, gender and fat %. Elevated serum IL-6 levels were associated with increased Glx levels in left HPC, left MTC, and right DLPFC, after processing the 1H-MRS data with Tarquin. Overall, the agreement between Tarquin and LCModel results was moderate to strong for tNAA, tCho, mIns and tCr, but weak to very weak for Glx. Peripheral inflammatory markers (IL-6 and kynurenine) were not associated with older age, higher fat %, decreased brain gray matter volume loss or decreased cognitive functioning. Conclusion: Our results suggest that serum kynurenine may be used as a peripheral inflammatory marker that is associated with neuroinflammation and neurodegeneration, although not linked to cognition. Future studies should consider longitudinal analysis to assess the causal inferences between chronic peripheral and neuroinflammation, brain structural and neurometabolic changes, and cognitive decline in aging.